A Linguistic Study of Speech Comprehension and Production in Aphasic Speakers - Minwas Jamal Rasheed; Lanja D. Dabbagh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
Language is a phenomenon that has a central point within the field of linguistics. Among many aspects that are usually tackled within linguistics, the comprehension and the production of language are analyzed as well. Therefore, the two mentioned processes have a specific focus within the domain of linguistics. The ability to produce and comprehend language is usually examined by the speech input and output of speakers with brain damage. The current research tries to highlight a linguistic investigation by focusing on the speech comprehension and production of individuals with aphasia. That is why the aim of this research is to analyze the linguistic matters of spoken language input and output that are usually weakened as an outcome of brain damage such as stroke. In addition, the present work tries to reveal possible characteristics of aphasic speakers that show clear difficulties during speech input and output due to brain injury. The method of the study consists of semi-structured interviews with aphasic speakers that are collected by visiting a number of different public and private hospitals and physiotherapy centers in Erbil. The tests are done by using picture presentation techniques and a questionnaire related to background information of the participants. Aphasic individuals are shown a number of different types of pictures and are asked to answer specific questions related to the events within the pictures. Their linguistic state is then examined by analyzing their answer syntactically and semantically.